Chirping Symphony of Nature in the Digital Art World: How Ecomusicology Cultivates EFL Students’ Nature Connectedness and Interests - Jepri Ali Saiful (Tell : Teaching of English Language and Literature Journal, 2024)
This study responds to the imperative for ELT’s explicit contribution to environmental sustainability. This study proposed and developed an ecomusicology instruction about Earth in ELT, exploring its impacts on EFL students’ nature connectedness and interests. Using mixed-method convergent research design, 11 participants, third-semester students in an English education department in Surabaya, Indonesia (comprising 3 males and 8 males, aged above 18) experienced the instruction for more than a week. Pre- and post-test surveys were administered to obtain quantitative data which were analyzed using Wilcoxon signed-rank test. Post-instruction, the students completed open-ended questionnaires for qualitative insights. Integrated results of quantitative and qualitative analyses revealed improvements in students’ nature connectedness and interests. The results suggest that the use of ecomusicology in teaching environmental issues in English lessons enhances EFL students’ unity with nature and strong nature interests. These results highlight a new avenue for the ELT field to address environmental issues by developing future citizens’ (EFL students) environmental sustainability values: nature connectedness and interests through ecomusicology instruction.